2021
DOI: 10.3390/app11136171
|View full text |Cite
|
Sign up to set email alerts
|

Experimental Study on Two PCM Macro-Encapsulation Designs in a Thermal Energy Storage Tank

Abstract: The use of latent heat thermal energy storage is an effective way to increase the efficiency of energy systems due to its high energy density compared with sensible heat storage systems. The design of the storage material encapsulation is one of the key parameters that critically affect the heat transfer in charging/discharging of the storage system. To fill the gap found in the literature, this paper experimentally investigates the effect of the macro-encapsulation design on the performance of a lab-scale the… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

0
9
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 24 publications
(9 citation statements)
references
References 34 publications
0
9
0
Order By: Relevance
“…On the other hand, when the PCM balls were located at the upper position in the tank, they contributed to mixing the water. The implementation of PCM in the storage tank was intensively focused because it could take more advantage of latent heat thermal energy storage than sensible heat storage [16][17][18]. Verez et al [17] designed a PCM slab to investigate the effect of PCM slab thickness on temperature stratification.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…On the other hand, when the PCM balls were located at the upper position in the tank, they contributed to mixing the water. The implementation of PCM in the storage tank was intensively focused because it could take more advantage of latent heat thermal energy storage than sensible heat storage [16][17][18]. Verez et al [17] designed a PCM slab to investigate the effect of PCM slab thickness on temperature stratification.…”
Section: Introductionmentioning
confidence: 99%
“…The implementation of PCM in the storage tank was intensively focused because it could take more advantage of latent heat thermal energy storage than sensible heat storage [16][17][18]. Verez et al [17] designed a PCM slab to investigate the effect of PCM slab thickness on temperature stratification. The study found that the thickness of the PCM slab affected temperature stratification, with different magnitudes dependent on the flow rate.…”
Section: Introductionmentioning
confidence: 99%
“…Substantial research on different types of PCMs for hot and cold stores is available in the literature [6], [7]. For instance, the use of paraffin wax has been reported several years ago [8], [9].…”
Section: Introductionmentioning
confidence: 99%
“…What is more important to be concerned about than those challenges is the cost of production of batteries. However, there is a chance in the future that production costs would be lower as the method of battery production is improved [12][13][14][15][16][17][18][19][20][21][22][23].…”
Section: Introductionmentioning
confidence: 99%
“…What is more important to be concerned about than those challenges is the cost of production of batteries. However, there is a chance in the future that production costs would be lower as the method of battery production is improved [12][13][14][15][16][17][18][19][20][21][22][23]. Technology Description Basic Process is a theory which describes the thermodynamic cycle for the steam turbine which is known as the Rankine cycle [24][25][26].…”
Section: Introductionmentioning
confidence: 99%